PEMBELAJARAN KONTEKSTUAL BERBASIS ETNOMATEMATIKA DALAM MENINGKATKAN HASIL BELAJAR SISWA DITINJAU DARI KEMAMPUAN MATEMATIS - Finsensius Yesekiel Naja; Agustina Mei; Sofia Sa'o (Program Studi Pendidikan Matematika, 2022)
Learning mathematics must be related to the real context of everyday life. Contextual learning is learning within the context of everyday life, ethnomathematics is the knowledge that links mathematics with cultural elements, and ethnomathematics is the concept of knowledge about the development of mathematics in various cultures. This study aims to improve students' activities and learning outcomes through ethnomathematical-based contextual learning in terms of students' mathematical abilities. This type of research is classroom action research with four stages, namely planning, implementation, observation, a reflection which is carried out in two cycles. Data were obtained from instruments in the form of rubrics for assessing students' mathematical abilities and tests to determine student learning outcomes. The subjects in this study were class VII students of SMP Negeri 2 Ende Selatan, totaling 20 people. The data analysis technique used a comparative descriptive technique between cycles. The results showed that: (1) there was an increase in students' mathematical abilities from the initial conditions, cycle 1, and cycle 2. In the initial conditions students' mathematical abilities averaged 48%, with the implementation of the model in cycle 1 65%, and in cycle 2 80 %. (2) student learning outcomes have also increased. In the initial condition, only 37% of students experienced completeness, in cycle 1 it increased to 65% of students who completed, and in cycle 2 it increased to 86%.